Electrical power systems - Murty, P. S. R. (Butterworth-Heinemann, an imprint of Elsevier, 2017)
Electrical Power Systems provides comprehensive, foundational content for a wide range of topics in power system operation and control. With the growing importance of grid integration of renewables and the interest in smart grid technologies it is more important than ever to understand the fundamentals that underpin electrical power systems. The book includes a large number of worked examples, and questions with answers, and emphasizes design aspects of some key electrical components like cables and breakers. The book is designed to be used as reference, review, or self-study for practitioners and consultants, or for students from related engineering disciplines that need to learn more about electrical power systems.